(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
It is a matter of honour for me to write this editorial for Journal of Pakistan Orthopaedic Association (JPOA). In my short carrier of more than two decades in Pakistan, I have seen Orthopaedic grow from trauma service and few individual shining stars to rapid growth of orthopaedic subspecialty. This trend is spreading to all major cities of Pakistan. The opportunities for young orthopaedic surgeons have never been so widespread. Orthopaedics is passion and is not for the faint at heart. So, I believe and so was my motto when I took onto orthopaedic surgery as a career. I have come a long way down the road and as immediate past president of Pakistan Orthopaedic Association (POA), it is a matter of immense pleasure for me to have represented the orthopaedic fraternity of this country at the highest possible level. I have represented Pakistan internationally at various orthopaedic congresses at USA, Australia, UK, Turkey, Singapore, China and Malaysia.